Association of Low Birth Weight and Preterm Birth With the Incidence of Knee and Hip Arthroplasty for Osteoarthritis. Issue 4 (April 2015) - Hussain, Sultana Monira; Wang, Yuanyuan; Wluka, Anita E.; Shaw, Jonathan E.; Magliano, Dianna J.; Graves, Stephen; Cicuttini, Flavia M.
Abstract : Objective: Low birth weight (LBW) and preterm birth have been associated with adverse adult outcomes, including hypertension, insulin resistance, cardiovascular disease, and reduced bone mass. It is unknown whether LBW and preterm birth affect the risk of osteoarthritis (OA). This study aims to examine whether LBW and preterm birth were associated with the incidence of knee and hip arthroplasty for OA. Methods: A total of 3, 604 participants of the Australian Diabetes, Obesity and Lifestyle Study who reported their birth weight and history of preterm birth and were age >40 years at the commencement of arthroplasty data collection comprised the study sample. The incidence of knee and hip replacement for OA during 2002–2011 was determined by linking cohort records to the Australian Orthopaedic Association National Joint Replacement Registry. Results: One hundred and sixteen participants underwent knee arthroplasty and 75 underwent hip arthroplasty for OA. LBW (yes versus no; hazard ratio [HR] 2.04, 95% confidence interval [95% CI] 1.11–3.75, P = 0.02) and preterm birth (yes versus no; HR 2.50, 95% CI 1.29–4.87, P = 0.007) were associated with increased incidence of hip arthroplasty independent of age, sex, body mass index, education level, hypertension, diabetes mellitus, smoking, and physical activity. No significant association was observed for knee arthroplasty. Conclusion: Although these findings will need to be confirmed, they suggest that individuals born with LBW or at preterm are at increased risk of hip arthroplasty for OA in adult life. The underlying mechanisms warrant further investigation.